(untitled) (Efficient: Indonesian Journal of Development Economics, 2026)
Higher education is a primary pillar of modern economic development, playing a crucial role in knowledge development, human capital formation, and innovation creation. In a knowledge-based economy, universities function not only as educational institutions but also hold a strategic role in research, technological innovation, and cross-sector collaboration through models such as the Multi-Helix. This study employs a Systematic Literature Review (SLR) approach and bibliometric analysis using the PRISMA method on 128 Scopus-indexed articles from the 2015–2025 period. The analysis was conducted to map publication trends, geographical distribution, collaboration networks, and key research themes using VOSviewer software. The results indicate that publication trends increased significantly after 2022, reaching a peak in 2024, with dominant contributions from European countries, particularly the United Kingdom, as well as China, Italy, and Spain. Central themes dominating the literature include "economic growth" and "innovation," which are linked through mechanisms of human capital, academic entrepreneurship, technology transfer, and the development of innovation ecosystems. Higher education plays a strategic role in driving innovation and economic growth by strengthening university innovation capacity, fostering cross-actor collaboration, developing entrepreneurial ecosystems, and improving the quality and distribution of human capital. However, these contributions are highly dependent on the regional context, institutional governance, integration with public policy, and the ability to effectively measure and manage the impact of innovation.